Thyroid cancer survival and prognostic factors in Yantai, China (2012–2022): a population-based study - Haiyun Liu; Shuxia Zhang; Xiaohui Liu; Qianqian Wang; Hongjie Zhang; Weihong Cui (BMC Cancer)
Abstract Background Although thyroid cancer is associated with low mortality rates, significant racial disparities in thyroid cancer outcomes have not been adequately studied in Asia. Moreover, the Asian population consists of different ethnic groups that are not homogeneous. This study aimed to perform a population-based analysis of survival outcomes and prognostic factors in thyroid cancer patients. Methods The demographic data and tumor characteristics of all the thyroid cancer patients identified were obtained from the Yantai Cancer Registry. The thyroid cancer-specific death risk in patients was evaluated using the proportion of deaths, standardized mortality ratio (SMR) and absolute excess risk (AER). The Kaplan‒Meier method and the Cox proportional hazards regression model were used to evaluate overall survival (OS) and prognosis. Results A total of 10,852 new cases of thyroid cancer occurred with a 5-year OS of 96.20% in Yantai from 2012 to 2022. The SMR decreased from 1.06 (95%CI: 0.93 − 1.33) in 2012 to 0.50 (95%CI: 0.42 − 0.63) in 2022 and the AER decreased from 11.07 (95%CI: -13.42 − 47.39) per 10,000 population in 2012 to -105.02 (95%CI: -149.53 − -63.02) per 10,000 population in 2022. Disparities in the OS of thyroid cancer patients were found across different diagnosis periods, genders, age groups, places of residence, occupational classes, tumor sites and sizes, cervical lymph node metastasis statuses, TgAb levels, pathological types, clinical stages and treatment timings (all p < 0.05). Multivariate analysis showed that age group (≥ 65 years: HR = 1.727), tumor site (location in the isthmus: HR = 3.117), tumor size (> 3 cm: HR = 3.170), cervival lymph node metastasis (HR = 1.876), TgAb levels (115 − 500 IU/ml: HR = 7.103; > 500 IU/ml: HR = 13.554), pathological types (MTC: HR = 2.060; ATC: HR = 10.747), clinical stages (stage II: HR = 2.224; stage III: HR = 3.361; stage IV: HR = 3.494), treatment timing (> 3 months: HR = 2.594), diagnosis period (2017 − 2022: HR = 0.633) and gender (female: HR = 0.711) were found to be associated with the risk of death; after stratified adjustment, significant differences in prognostic factors were identified among thyroid cancer patients with varying pathological types. Conclusion The risk of death from thyroid cancer in Yantai has significantly decreased and the OS of patients has improved significantly in the past decade. The prognosis of thyroid cancer in this area was notably impacted by various factors and the resolution of survival study outcomes for thyroid cancer patients should be enhanced.